Lifetime Measurement of Highly Charged Ions Relevant to Astrophysics (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
We have measured the \(\rm 1s2s2p ~^4P^0_{5/2}\)-\(\rm 1s^22s~^2S_{1/2}\) magnetic quadrupole X-ray transition energy in Li-like Fe along with the \(\rm 1s2s~^3S_1\)-\(\rm 1s^2~^1S_0\) transition energy in He-like Fe using multi channel doppler tuned spectrometer. These states have been produced through the interaction of 165 MeV Fe\(^{12+}\) ion beam with 100 \(μ\)g/cm\(^2\) thin carbon foil. Further we have measured the lifetime of \(\rm 1s2s2p ~^4P^0_{5/2}\) level in Li-like Fe. The measured transition energy of \(\rm 1s2s~^3S_1\)-\(\rm 1s^2~^1S_0\) is in good agreement with the available theoretical predictions and experimental measurements, whereas the measurement of \(\rm 1s2s2p ~^4P^0_{5/2}\)-\(\rm 1s^22s~^2S_{1/2}\) energy is little lower than the theoretical estimations. However, the measured lifetime of \(\rm 1s2s2p ~^4P^0_{5/2}\) level compares well with the theoretical predictions.
Keywords: X-rays; atomic data; Atomic processes; Line; formation